Career or Flexible Work Arrangements? Gender Differences in Self-Employment in a Young Market Economy - Dominik Buttler; Eva Sierminska (Institute of Labor Economics (IZA), 2019)
We examine supply-side determinants of transition from the wage and salary sector to self-employment of women and men living Poland. The empirical analysis is made possible due to a unique and under explored longitudinal survey – Social Diagnosis – that contains rare indicators such as job preferences and work events. The empirical results in the 2007-2015 period indicate that women and men transitioning into self-employment are differently motivated. In terms of job attributes, women find independence at work and for those in professional occupations a job matching their competences as a desirable job attribute, while for men the lack of stress, a good salary and independence is key. The analysis of work events and its influence on self-employment weakly confirms the glass-ceiling hypothesis. In line with other research, our analysis indicates that financial constraints strongly determine the entry into self-employment. A key human capital determinant is past entrepreneurial experience indicating a slow, cautious transition process into self-employment.
Keywords: D31; G11; J61; 330; risk; self-employment; work conditions; gender; Poland